Automatic material vibration feeding system - ZHOU MIN; PAN JIAFU (2022)
The utility model relates to the technical field of feeding systems, and discloses an automatic material vibration feeding system. The device comprises a bottom plate and two sets of side plates which are oppositely arranged, a conveying device is arranged on one side between the two sets of side plates, a partition plate is fixedly connected to the upper surface of the conveying device, fixing plates are welded to the outer surfaces of the two sides, close to the side plates, of the partition plate, and the outer surfaces of the sides, away from the partition plate, of the fixing plates are welded to the sides, close to the partition plate, of the side plates. A hydraulic cylinder is welded to the upper surface of the bottom plate, a clamping groove is formed in the lower surface of the side plate, a second fixing block is slidably connected into the clamping groove of the side plate, and the output end of the hydraulic cylinder is welded to the lower surface of the second fixing block. Therefore, the situat